2018
DOI: 10.1002/cplu.201800194
|View full text |Cite
|
Sign up to set email alerts
|

Organoruthenium and Organoosmium Complexes of 2‐Pyridinecarbothioamides Functionalized with a Sulfonamide Motif: Synthesis, Cytotoxicity and Biomolecule Interactions

Abstract: Anticancer‐active RuII–η6‐p‐cymene complexes of bioactive 2‐pyridinecarbothioamide ligands have been shown to have high selectivity for plectin and can be administered orally. Reported herein is the functionalization of a 2‐pyridinecarbothioamide with a sulfonamide group and its conversion into M–η6‐p‐cymene complexes (M = Ru, Os). The presence of a sulfonamide moiety in many organic drugs and metal complexes endows these agents with interesting biological properties and can transform the latter into multi‐tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
(109 reference statements)
2
4
0
Order By: Relevance
“…The spectra featured peaks at m/z values assignable to the [M − X] + ions while the base peak was attributed to the [M − 2X − H] + ions. A similar ionization behavior in ESI-MS was observed for other PCA-metal complexes [34,35,37,38]. The experimental m/z values as well as the isotopic distribution pattern closely resembled the calculated values.…”
Section: Resultssupporting
confidence: 80%
“…The spectra featured peaks at m/z values assignable to the [M − X] + ions while the base peak was attributed to the [M − 2X − H] + ions. A similar ionization behavior in ESI-MS was observed for other PCA-metal complexes [34,35,37,38]. The experimental m/z values as well as the isotopic distribution pattern closely resembled the calculated values.…”
Section: Resultssupporting
confidence: 80%
“…Acetazolamide, methazolamide, ethoxzolamide, saccharin, brinzolamide, and dorzolamide molecules inhibit CAs. , Among the various isoforms of CAs, it is now thought that CA IX and CA XII are two membrane-bound isoforms that help to control the pH of cancer cells in a hypoxic environment. Thus, hypoxia-inducible CA IX appears to be a promising target for anticancer therapy because of its overexpression in many cancer cells compared to normal cells. The activity of CA targeting sulfonamides may be modified and improved upon binding to transition-metal ions. , It was recently shown that 4-(2-aminoethyl)­benzenesulfonamide (AEBS)-bound gold nanoparticles selectivity target CA IX over CA I and CA II . Hence, sulfonamides have the scope to target cancer cells over normal cells selectively.…”
Section: Introductionmentioning
confidence: 99%
“…105 Therefore, benzene sulfonamides are a wellknown class of CA inhibitors and have been recently applied for targeted anti-tumor metallodrug construction. [106][107][108][109][110][111] For instance, our group developed rhenium(I) tricarbonyl complex 2-60 that is functionalized with a terthiophene group for photodynamic therapy (PDT) and a benzene sulfonamide for CA IX inhibition (Fig. 16(a)).…”
Section: Enzymes and Proteinsmentioning
confidence: 99%